Broken abacus? a more accurate gauge of China's economy - Rosen, Daniel H.; Bao, Beibei (CSIS report, 2015)
This study reassesses China's nominal economic size from the bottom up. It compares China's practices with international standards and reviews the long-standing arguments about Chinese economic statistics to separate real concerns from distractions